No clinical or biological difference between Chikungunya and Dengue Fever during the 2010 Gabonese outbreak - Dieudonne Nkoghe (Infectious Disease Reports, 2012)
Chikungunya (CHIKV) and Dengue (DENV) viruses, both arboviruses, have caused multiple outbreaks worldwide. Their clinical features are poorly described in Africa and there is no comparative study, although Chikungunya is considered as a dengue-like disease. We conducted a comparative study of clinical and biological data from CHIKV and DENV positive patients during the 2010 Gabonese outbreak. Patients consulting with general symptoms and having laboratory confirmation for CHIKV or DENV were included. Clinical and biological data were recorded. Statistical analyses were performed using Epi Info. A P value < 0.05 was considered significant. In all, 270 CHIKV+, 53 DENV+ and 20 co-infected patients were included in the study. Headaches, hemorrhage, leukopenia and lymphopenia were significantly (P respectively 0.01, 0.001, 0.02 and 0.001) more frequent in DENV+ patients than in CHIKV+. There was no additive effect of the two viruses. These clinical and hematological disorders are non specific and cannot assist for the differential diagnosis. These diseases are clinically indistinguishable, and need for laboratory confirmation.